The relationship between family’s use of English at home with students’ proficiency in the language. - Syed Uzir, Sharifah Fatin Athira; Mohamed Salleh, Rabiah Tul Adawiyah (Universiti Teknologi MARA Perak Branch, 2019)
In Malaysia, English is considered a ‘strong’ second language (Azman, 2016). Realising the importance of English, many Malaysian families opt to speak English at home, even though English is not their first language (Hashim, 2014; Mohamed Salleh, Kawaguchi, Jones, & Biase, 2016; Salehuddin, 2012). Therefore, this paper aims to examine the correlation between home factor and ESL students’ proficiency in the language. The participants were three bilingual Malay-English students studying at International Islamic University Malaysia (IIUM). Each family of the student practices different communication strategy at home; the first family uses the acrolect variety of Malaysian English (ME), the second family uses the mesolect variety of ME and the third family does not use English at all. Data regarding the family’s use of English were obtained via questionnaires and the proficiency of the students were measured from the English proficiency test, taken from the University of Michigan database. The results show that the differences between the students’ English proficiency were not noticeably different as all of them scored above 80% in the test. The findings indicate that there might be other external variables responsible for the students’ proficiency in English other than the home factor.